RESEARCHING MISLEADING INFORMATION WITHIN HYBRID MEDIA ECOLOGIES. WHERE WE ARE AND WHERE WE ARE GOING - Giglietto, Fabio; Valeriani, Augusto; Iannelli, Laura; Rossi, Luca; Dvir Gvirsman, Shira; Zeng, Jing; Chan, Chung-hong; Fu, King-wa; Farkas, Johan; Schou, Jannick (AoIR Selected Papers of Internet Research, 2016)
On friday November 13, a group of coordinated attacks hit Paris causing more than 130 victims. The frantic moments following the first fragmented news, the spread of rumors and the wide media coverage of the following days, highlighted all the strength and fragility of an hybrid media system in which new and old media logics compete and integrate. During the hours following the attacks, we have witnessed the spread of testimonies published on social media and widely diffused by legacy media, we have observed the emergence of forms of cooperation aimed at supporting the search for the missing and we have participated in the ritual of collective mourning with the hashtag #PrayforParis. At the same time, however we have also read numerous reports that, although eventually proved to be false, have contributed to shape the representation of those events. Contemporary information ecologies, by simplifying processes of production and circulation of news, could also facilitate the diffusion of false information and/or unverified news. In this context, new digital elites (i.e. bloggers, social media power users etc.), legacy media actors and non-elites are still in search of a strategy for real time verification and debunking. Previous studies emphasized the importance of echo chamber effects and "confirmation bias" (the tendency to consider true information that confirms what we already believe true) as the cognitive process that, at the same time, makes misinformation easy to spread and difficult to debunk. Peer networks play an important role as a source of confirmation or disconfirmation of rumors. As a result, homophilic and polarized communities represent a fertile ground for disinformation. Recent studies also pointed out the combined effect of "confirmation bias" and online communities often characterized by a high degree of homogeneity. While widely analyzed from different disciplines, both the studies on spread of rumors, and false or misleading information still lack that level of conceptual coherence that would allow different approaches and academic backgrounds to fruitful collaborate. Recognizing this limit, several defining attempts have been carried on. By pinpointing the limits of existing predominantly actor-oriented taxonomies when applied to hybrid media ecologies, the first paper in this panel introduces an alternative process-based classification that distinguishes between “mis-information” (where a false information generated by a third actor is, in a short run, picked up and diffused by mainstream media, without verification and producing legitimization), “pseudo-information” (where “alternative” media sources produce information aimed at correcting the mainstream media system by giving voices to alternative takes on reality considered not adequately represented by traditional media) and “fake-information” (in which media actors specialized in the production of false information injects fake-news, mainly within social media ecologies for propaganda, to get attention and clicks, to earn revenues from online ads). The three following papers further elaborate on each of those category: By presenting a new model of news flow in the hybrid media ecologies, the second paper in this panel will dig deeper and shed more light on the processes behind “mis-information” with a specific focus on the effects of the SNS proliferation on news production, and especially on the quality and diversity of the information presented. The third paper in this panel discusses the role played by social media as platforms where news as well rumours circulates in response to a lack of transparency on mainstream media. The empirical analysis of the conversations originated on Weibo by the 2015 devastating explosions in Tianjin - northern China -, highlights an alternative take on the beneficial role of “pseudo-information” as a form of counter-power against the ruling regime in authoritarian contexts. The fourth and last paper, presents the findings from a multi-sided online ethnographic study of 12 Danish Facebook pages that during 2015, claimed to be run by radical Islamists living in Denmark and through aggressive and violent language, proclaimed that Muslims in the country were plotting to destroy the Danish society from within. Contents created by this orchestrated campaign of “fake-information”, received thousands of comments the majority of which contained counter-aggression towards not only the page admins but also Muslims and immigrants in general. This massive user attention turned the pages into sites of aggression and xenophobia, making them part of a much larger discursive struggle to define the ‘’truth’’ about Muslims and immigrants in the country. Combined, these papers explore some of the ways in which theoretical and empirical scholarly investigations can open up paths for a new cross-disciplinary research agenda on the spread of misleading information in contemporary hybrid media ecologies.